Where should I study? : international students’ perceptions of higher education in the UK, Ireland, and the U.S. - Rounsaville, Cheryl A. (2012)
In the thesis I examine international student decision-making arguing that there is a gap in knowledge about the theoretical frameworks which have been applied to understanding this issue. A comprehensive review of the literature showed that thus far the foremost theory utilised for explaining international student decision-making is the Push-Pull Theory of Migration, a theory which is primarily quantitative. This research innovatively uses a theoretical framework combining three influential capital theories based on a qualitative methodology. Using this theoretical framework, I sought a deeper, and potentially new and different understanding of why international students choose to study abroad and why they select particular host countries – the two questions traditional Push-Pull Theory seeks to answer.